Hormoligosis Evaluation and Efficacy of Fenoxycarb on the Cotton Mealybug (Phenacoccus solenopsis) - Idrees,Muhammad (2022)
Abstract Sublethal dilutions exhibited hormoligosis when they were exposed to the different levels of pesticides. The present study was designed to check the efficacy and hormoligosis of fenoxycarb on four generations of cotton mealybug. The experiment was performed in the laboratory conditions at department of Entomology, University of Agriculture, Faisalabad. After 3 days, treatments showed statistically considerable differences (P ˂ 0.05) and maximum mortality was recorded at the highest dose level of fenoxycarb. After 7 days, the treatments had significant differences (P ˂ 0.05). The greater mortality (89.02%), fecundity (143.66%) and longevity (39.62%) was recorded at a concentration of fenoxycarb 2.4%. Laboratory bioassay showed that after 3 days of experiment, fenoxycarb was less effective at concentration LC10 (0.17 ppm) (0.03-0.36), while after 7-days result was LC10 (0.08 ppm) (0.05-0.12). The 1st instar showed maximum mortality at the concentration (LC50 = 10.02%). The maximum fecundity and longevity were found in control. The sex ratio was higher in control while the minimum at (LC10 = 0.17%). At 3 days, hormoligosis was observed in fecundity at LC10 (0.17%) in G1 (52.28) and in G4 (58.27) while LC50 (10.02%) in G1 (37.84) and G4 (42.73). At 7 days PAI of LC10 (0.01%) in G1 (58.61) and in G4 (63.50) while LC50 (0.39%) in G1 (37.67) and in G4 (44.89). The management of the insect pest in the cotton crop depends mainly on how we are using these chemicals.